Dystonia in neurodegeneration with brain iron accumulation: outcome of bilateral pallidal stimulation - Timmermann, L.; Pauls, K. A. M.; Wieland, K.; Jech, R.; Kurlemann, G.; Sharma, N.; Gill, S. S.; Haenggeli, C. A.; Hayflick, S. J.; Hogarth, P.; Leenders, K. L.; Limousin, P.; et al. (OXFORD UNIV PRESS, 2010)
Neurodegeneration with brain iron accumulation encompasses a heterogeneous group of rare neurodegenerative disorders that are characterized by iron accumulation in the brain. Severe generalized dystonia is frequently a prominent symptom and can be very disabling, causing gait impairment, difficulty with speech and swallowing, pain and respiratory distress. Several case reports and one case series have been published concerning therapeutic outcome of pallidal deep brain stimulation in dystonia caused by neurodegeneration with brain iron degeneration, reporting mostly favourable outcomes. However, with case studies, there may be a reporting bias towards favourable outcome. Thus, we undertook this multi-centre retrospective study to gather worldwide experiences with bilateral pallidal deep brain stimulation in patients with neurodegeneration with brain iron accumulation. A total of 16 centres contributed 23 patients with confirmed neurodegeneration with brain iron accumulation and bilateral pallidal deep brain stimulation. Patient details including gender, age at onset, age at operation, genetic status, magnetic resonance imaging status, history and clinical findings were requested. Data on severity of dystonia (Burke Fahn Marsden Dystonia Rating Scale-Motor Scale, Barry Albright Dystonia Scale), disability (Burke Fahn Marsden Dystonia Rating Scale-Disability Scale), quality of life (subjective global rating from 1 to 10 obtained retrospectively from patient and caregiver) as well as data on supportive therapy, concurrent pharmacotherapy, stimulation settings, adverse events and side effects were collected. Data were collected once preoperatively and at 2-6 and 9-15 months postoperatively. The primary outcome measure was change in severity of dystonia. The mean improvement in severity of dystonia was 28.5\% at 2-6 months and 25.7\% at 9-15 months. At 9-15 months postoperatively, 66.7\% of patients showed an improvement of 20\% or more in severity of dystonia, and 31.3\% showed an improvement of 20\% or more in disability. Global quality of life ratings showed a median improvement of 83.3\% at 9-15 months. Severity of dystonia preoperatively and disease duration predicted improvement in severity of dystonia at 2-6 months

this failed to reach significance at 9-15 months. The study confirms that dystonia in neurodegeneration with brain iron accumulation improves with bilateral pallidal deep brain stimulation, although this improvement is not as great as the benefit reported in patients with primary generalized dystonias or some other secondary dystonias. The patients with more severe dystonia seem to benefit more. A well-controlled, multi-centre prospective study is necessary to enable evidence-based therapeutic decisions and better predict therapeutic outcomes.
Keywords: Neurodegeneration with brain iron accumulation; dystonia; deep brain stimulation; globus pallidus